Death in the Archives: Witnessing War in Ireland, 1919–1921. Issue 1 (3rd March 2021) - Dolan, Anne
Abstract: In a relatively brief, not very lethal, but meticulously documented guerrilla war in Ireland there is an opportunity to reflect on who historians choose to listen to when writing about violence. Across 1920–21 thousands of inquests captured the voices of the men, women and sometimes children who were the first to describe and define the act of killing in this conflict, but who very quickly fell out of the historical record after that point. This article considers the contribution these bystanders can make to a history of violence, and some of the challenges their evidence presents. By witnessing death were they an integral part of how killing was meant to be understood? Are they fundamental to an understanding of how terror worked, and did they, by their presence, by the way they spoke of what they saw, contribute to why so few deaths were needed for the message to be understood in the Irish context? Ultimately, these witnesses also raise questions about the reactions they prompted then as well as now. Is it easier to hear of killing from a combatant than from a child, and are there consequences for the history of violence in the making of that choice?